The experience of women who delivered during the first wave of COVID-19 pandemic in Belgium: a retrospective studyAJOG Global Reports at a Glance - Ahmed Wafi, MD; Jerome Rosetti, MD; Michael De Brucker, MD, PhD; Iris Mezela, MD; Nouhaila Abbib, MD; Jacques C. Jani, MD, PhD; Dominique A. Badr, MD (Elsevier, 2023)
BACKGROUND: The lockdown caused by the COVID-19 pandemic has imposed some restrictions on hospital activities, requiring medical staff to find efficient alternatives to ensure adequate medical care for patients. OBJECTIVE: This study aimed to investigate the experience of pregnant women who delivered during the first wave of COVID-19, and to evaluate the impact of COVID-19-related restrictions. STUDY DESIGN: This was a retrospective multicenter study. All pregnant women who delivered a live infant between March 20, 2020 and June 20, 2020 were evaluated using a 35-item survey at 1 year following delivery. Each patient was contacted via 3 modalities. Patients who reported that their prenatal follow-up was interrupted were compared with those who reported that their prenatal follow-up was unchanged. Among 1096 patients who delivered a live infant across the 3 participating centers during the study period, 389 responses were needed for an estimated margin of error of 4%. RESULTS: A total of 469 of 1096 (42.8%) patients answered the survey, of whom 151 (32.2%) reported that the follow-up of their pregnancy was interrupted (exposed group) and 318 (67.8%) reported that their follow-up was maintained as normal (unexposed group). The rate of presentation to the emergency department was higher in the exposed group than in the unexposed group (P=.001). The level of dissatisfaction was also higher in the exposed group, and patients in this group would have postponed their pregnancy if they had known about the pandemic in advance (P<.001 and P=.001, respectively). CONCLUSION: Interruption and modification of antenatal follow-up in pregnant women is associated with patient dissatisfaction and increased presentation to the emergency department.